2012
DOI: 10.1080/17439760.2012.667144
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a yoga-based intervention for young adults on quality of life and perceived stress: The potential mediating roles of mindfulness and self-compassion

Abstract: 2012)Effects of a yoga-based intervention for young adults on quality of life and perceived stress: The potential mediating roles of mindfulness and self-compassion, The Journal of Positive Psychology: Dedicated to furthering research and promoting good practice, 7:3, 165-175,The purpose of this pilot study was to investigate the effects of a yoga-based program on quality of life, perceived stress, mindfulness, and self-compassion in young adults. These variables were measured in 33 self-selected participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(93 citation statements)
references
References 52 publications
5
83
1
Order By: Relevance
“…Extant literature attests to maladaptive cognitions as mediators of treatment change in CBT for anxiety disorders [20]. In virtue of the similarity between yoga and mindfulness based interventions, yoga likely conveys its effect by way of changes in mindfulness[21]. Basic research on yoga and its component techniques suggests it might facilitate reductions in arousal, targeting different mechanisms than does CBT [22–25].…”
Section: Introductionmentioning
confidence: 99%
“…Extant literature attests to maladaptive cognitions as mediators of treatment change in CBT for anxiety disorders [20]. In virtue of the similarity between yoga and mindfulness based interventions, yoga likely conveys its effect by way of changes in mindfulness[21]. Basic research on yoga and its component techniques suggests it might facilitate reductions in arousal, targeting different mechanisms than does CBT [22–25].…”
Section: Introductionmentioning
confidence: 99%
“…16 Mindfulness-based stress reduction (MBSR) reduced anxiety in veterans in a study conducted by Serpa JG, et al 17 Gard T, et al also concluded in their one study that yoga-based intervention decreases the perceived stress in young adults. 18 Messripour M, et al concluded in their one study involving young Iranian women that yoga decrease the PSS-10 score. 19 Sudarshan Kriya Yogic breathing alleviated everyday stress, post-traumatic stress, and stress-related medical illnesses in a study conducted by Brown RP, et al Strength-All subjects (male and female) included in study were staying within hostel of college.…”
Section: Discussionmentioning
confidence: 99%
“…A qualitative study showed that people experienced self-compassion as a "kind and active process" (Pauley & McPherson, 2010, p. 134). Both mindfulness and self-compassion promote well-being (Gard et al, 2012).…”
Section: Characteristics Of Self-compassionmentioning
confidence: 99%